PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA DI KECAMATAN KAIRATU - Tamalene, Hanisa (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service activities carried out in Kairatu District, West Seram Regency, aim to improve elementary school students' mathematical concept understanding skills by using the Project Based Learning (PjBL) model. Besides helping to improve students' understanding of mathematical concepts, this model also helps teachers in teaching other materials. The students involved in this activity came from 3 schools, namely SD Negeri 3 Kairatu, SD Inpres Kairatu, and SD Inpres Siompo. The community service method used is preparation by providing a pre-test, implementing PjBL in learning, providing projects for students to work on, and providing evaluations. The results obtained after implementing the PjBL model can be seen from the pre-test and post-test scores obtained by students in the three schools. Namely, SD Inpres Kairatu has an average pre-test score of 42.93 and a post-test of 74.26; for SD Inpres Siompo, the average pre-test score is 51.13 and the post-test is 76.65; while for SD Negeri 3 Kairatu, the average pre-test is 46.65 and the post-test is 74.07. According to these results, teachers can use the PjBL model in the learning process for other materials